(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The transition period in a child’s life, encompassing major life changes such as starting school, moving to a new home, or experiencing family changes, can be a significant source of stress. This article provides a comprehensive review of the various stressors that children may encounter during transition periods and examines the impact of these stressors on their physical, emotional, and psychological wellbeing. The article also explores strategies for identifying and mitigating stress in children during these transitional phases.